Use of light weight defliectometer (Dynamic plate load test) in characterization of calcareous and siliceous sands - Khalid Elbaz Ahmed; Amr Farouk Elhakim; Mohamed Ibrahim Amer (Cairo : Khalid Elbaz Ahmed, 2013)
The light weight deflectometer (LWD) is a hand portable device that was originally developed in Germany to measure the soil in situ LWD modulus . Typically this modulus is used to evaluate the subsoil degree of compaction and soil static modulus . That it is suitable for compaction quality control of soil - surfaced roads embankments and replacement fills
Thesis (M.Sc.) - Cairo University - Faculty of Engineering - Department of Civil Engineering
Issued also as CD
Keywords: California bearing ratio; Light weight defliectometer; Siliceous sands